Pemasaran Dan Persaingan Sofitel Bali Nusa Dua Beach Resort Sebagai Sebuah Atraksi Wisata - Poulsen, Malene Haahr; Bhaskara, Gde Indra (JURNAL DESTINASI PARIWISATA; Vol 7 No 2 (2019): VOL 7, NO 2 (2019): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2019)
This research takes place in Sofitel Bali Nusa Dua Beach Resort. It aims to analyse the marketing and competition of Sofitel Bali as a tourist attraction. This is achieved by using the concept of marketing mix and Porter ?s Five Forces. The research of a hotel as a tourist attraction is conducted, because a hotel does not only serve as a place to sleep, rather does it serve a bigger role in the destination by giving the tourist an experience based on the product offered. This research uses both qualitative and quantitative data collected through observation and interviews from primary and secondary sources. The result of the research shows that the marketing of Sofitel Bali Nusa Dua Beach Resort as a tourist attraction is based on the target group, which is family. The brunch includes food, drinks and other facilities, such as a playground, pool, beach and entertainment. The promotion mostly happens through word of mouth and digital marketing. The biggest competitors are St. Regis, Westin and W Seminyak. Some substitute products are high tea, Sunday markets, beach clubs and even other tourist attractions. Suppliers and buyers have great powers, but this has not caused any problems for Sofitel Bali. Some advice to be given to the management of the brunch at Sofitel Bali is to always motivate the employees, adapt the product to meet the needs of the target group, to promote the pool and beach as a part of the brunch, to maintain a good relationship with suppliers and always be aware of competitors and take advantage of the uniqueness of the brunch at Sofitel Bali by specializing further in culture and life style. Keywords : hotel, tourist attraction, marketing, Sofitel